Students’ Perception on Ted (Technology, Entertainment, And Design) Talks Video at English Education Program of Muhammadiyah University of Bengkulu - Esmiyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
TED is a series of informative, educational, and inspiring talks that present ideas worth spreading. Students have the opportunity to develop their speaking and listening skills. The aims of this research were to find out and describe at English Education Program students’ perception on TED talks videos. The design of this research was descriptive qualitative method. The subject of this research was the 5th semester students. The instrument used in collecting the data was the interview list with a recorder. The result of this research showed that the students’ perception on TED talks videos was positive. They have already known and watched TED talks videos. Those videos inspired and motivated and TED talks videos is easily accessible as a medium for students to learn English. Those videos can be used to learn and improve students’ speaking and listening skills, increase vocabulary and improve English pronunciation. It can be as a medium to learn public speaking, such as mastering stage skills, facial expressions, body language, and eye contact. TED talks videos also can be as a medium to learn good presentation. The researcher suggested for the students it’s better for them to use TED talks videos as a medium for learning English, especially speaking and listening skills. For the lectures, the TED talks videos can be used as a reference for teaching speaking and listening skills so that the media used is more diverse. Keywords: Students, Perception, TED